Pemimpin Perempuan dan Non-Muslim Perspektif Ulama Tiga Serangkai - Jamil, M.; Ja'far, Ja'far (Program Studi Filsafat Agama Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2018)
The issue of woman?s and non-Muslim?s leadership seems to be unrest debate in the Islamic world. In Indonesia, the Islamic liberal groups or the modernists will usually accept woman or non-Muslim for being leader of the Muslims community, while the Muslim traditionalists and radical groups will usually show their firm rejection. This study seeks to elaborate the thought of the three Muslim scholars in the Eastern Sumatera, i.e. Abdul Halim Hasan, Zainal Arifin Abbas, and Abdur Rahim Haitami about the leadership of woman and non-Muslim. The article will put the position of thought of these scholars among the discourse of the issue. Employing content analytical method, the study finds that the three scholars reject woman and non-Muslim for being leader, especially state leader, of the Muslims community. They argue that leadership is a privilege honored to man, not to woman. They also assert that principle foundation of the shar??a forbids the Muslims from designating non-Muslim as their leader, except within emergency condition. Although these three Muslim scholars have been mostly influenced by modern thought, they seem to hardly accept woman?s and non-Muslim?s leadership. The ideas they propose will, therefore, contradict to the ideas hold by the liberal Muslim groups or other proponents of democracy.